2012
DOI: 10.5713/ajas.2012.12058
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 70 Expression is Increased in the Liver of Neonatal Intrauterine Growth Retardation Piglets

Abstract: Intrauterine growth retardation (IUGR) leads to the dysfunction in digestive system, as well as the alteration in the expression of some functional proteins. Heat shock protein 70 (Hsp70) could be induced by various stress factors, but whether Hsp70 expression is changed in neonatal IUGR infants has not been demonstrated. This study was conducted to explore the expression of Hsp70 in the liver by using the IUGR piglet model. Liver and plasma samples were obtained from IUGR and normal birth weight (NBW) piglets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…The naturally-occurring IUGR pig was recognized as an ideal model for the study of human IUGR [ 2 ]. Based on our previous study, newborn IUGR piglets had fatty hepatic infiltrates and cytoplasmic vacuolization in the liver [ 3 ]. Investigation of the hepatic proteome also suggested that the IUGR fetus had a lower activity of lipoprotein lipase (LPL) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The naturally-occurring IUGR pig was recognized as an ideal model for the study of human IUGR [ 2 ]. Based on our previous study, newborn IUGR piglets had fatty hepatic infiltrates and cytoplasmic vacuolization in the liver [ 3 ]. Investigation of the hepatic proteome also suggested that the IUGR fetus had a lower activity of lipoprotein lipase (LPL) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In IUGR piglets, the higher susceptibility to infection or environmental changes could be due to an ineffective immune system and subnormal size and histopathology of the thymus (Cromi et al., ; Zhong et al., ). In IUGR piglets, an overexpression of heat shock protein 70 (a cytoprotective protein produced in response to different cellular stressor factors) has been found in association with impaired cellular immunity at the intestine and liver levels (Li, Zhong, Zhang, Wang, & Wang, ; Zhong, Wang, Zhang, & Li, ), which suggests an impaired immune function (Yuan et al., ).…”
Section: Intrauterine Growth Restriction (Iugr) Pigletsmentioning
confidence: 99%
“…Ekspresi Hsp-70 yang mengalami peningkatan pada janin tumbuh lambat diduga karena respons dari stres multipel. 5 Iskemia, hipoksia, dan peningkatan resistensi vaskular yang mengakibatkan kerusakan fungsi plasenta sebagian besar disebabkan oleh karena peningkatan stres oksidatif. Heat-shock protein-70 merupakan marker stres oksidatif, pada trofoblas ekspresinya meningkat pada kasus PJT dan preeklamsi dibandingkan dengan trofoblas hamil normal.…”
Section: 4unclassified